2016
DOI: 10.7717/peerj.2593
|View full text |Cite
|
Sign up to set email alerts
|

Who’s your mama? Riverine hybridisation of threatened freshwater Trout Cod and Murray Cod

Abstract: Rates of hybridization and introgression are increasing dramatically worldwide because of translocations, restocking of organisms and habitat modifications; thus, determining whether hybridization is occuring after reintroducing extirpated congeneric species is commensurately important for conservation. Restocking programs are sometimes criticized because of the genetic consequences of hatchery-bred fish breeding with wild populations. These concerns are important to conservation restocking programs, including… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Calling quality was assured by high average read depth per locus. This process is similar to that used in published literature using DArTseq ™ SNPs from animal genetic samples (e.g., Couch et al, 2016;Donnellan et al, 2015).…”
Section: Snp Genotypingmentioning
confidence: 98%
See 1 more Smart Citation
“…Calling quality was assured by high average read depth per locus. This process is similar to that used in published literature using DArTseq ™ SNPs from animal genetic samples (e.g., Couch et al, 2016;Donnellan et al, 2015).…”
Section: Snp Genotypingmentioning
confidence: 98%
“…DArTseq ™ technology has been tested and used successfully for a wide range of genomic studies across a variety of vertebrate species (Melville et al, 2017). Examples of this include Cunningham's skinks (Egernia cunninghami) (Ofori, Beaumont, & Stow, 2017), North American green frog (Rana clamitans) (Lambert, Skelly, & Ezaz, 2016), trout cod (Maccullochella macquariensis) and Murray cod (Maccullochella peelii) (Couch, Unmack, Dyer, & Lintermans, 2016), yellowfin tuna (Thunnus albacares) (Grewe et al, 2015), eastern yellow robin (Eopsaltria australis) (Morales et al, 2017), and southern fiddler rays (Trygonrrhina dumerilii) (Donnellan et al, 2015).…”
Section: Snp Genotypingmentioning
confidence: 99%
“…Comprehensive monitoring of the lower Ovens River demonstrated the benefits of a long-term stocking program, with wide variation in the contribution of individual stocking events to the resultant population (Lyon et al, 2012). Genetic analysis of upper Murrumbidgee cod larvae from 2011 -2013 found hybridization between Trout cod and Murray cod, (Couch et al, 2016) demonstrating the problem of reestablishing a threatened species into the range of an established congeneric.…”
Section: Installing Woody Habitat © Martin Casey Fishesmentioning
confidence: 99%
“…However, recent broadscale genetic studies of Australian freshwater fishes have revealed high levels of genetic structuring between populations as well as many new cryptic species (Hammer et al, ; Hammer, Adams, Unmack, & Walker, ; Unmack, ; Unmack, Allen, & Johnson, ; Unmack & Dowling, ). As a result, introgressive hybridisation caused by introductions of “native” species outside their natural range or from one part of a species range to another, is a more recently recognised threat to the conservation for Australian freshwater fishes (Couch, Unmack, Dyer, & Lintermans, ; Harris, ; Lintermans et al, ). Keeping Australian fish in aquariums, ponds and stock troughs is becoming increasingly popular (e.g., Australia New Guinea Fishes Association).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, introgressive hybridisation caused by introductions of "native" species outside their natural range or from one part of a species range to another, is a more recently recognised threat to the conservation for Australian freshwater fishes (Couch, Unmack, Dyer, & Lintermans, 2016;Harris, 2013;Lintermans et al, 2005).…”
mentioning
confidence: 99%